2022
DOI: 10.3390/foods11030260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Pressure Processing on Fresh Sea Urchin Gonads in Terms of Shelf Life, Chemical Composition, and Microbiological Properties

Abstract: Paracentrotus lividus is a widespread sea urchin species appreciated worldwide for the taste of its fresh gonads. High-pressure processing (HPP) can provide a thermal equivalent to pasteurization, maintaining the organoleptic properties of the raw gonads. This study evaluated HPP technology’s effect at 350 MPa and 500 MPa on microbial inactivation and biochemical characteristics of P. lividus gonads. HPP at 350 MPa resulted in a higher decrease in protein and free amino acids associated with a loss of olfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It proved that TBARS values were not the key indicator to detect freshness of sea urchin gonads. Coroneo, Corrias, Brutti, Addis, Scano, and Angioni (2022) reported that the sea urchin gonads had high protein content and low lipid content. It would be the reason why the TBARS value was not critical.…”
Section: Resultsmentioning
confidence: 99%
“…It proved that TBARS values were not the key indicator to detect freshness of sea urchin gonads. Coroneo, Corrias, Brutti, Addis, Scano, and Angioni (2022) reported that the sea urchin gonads had high protein content and low lipid content. It would be the reason why the TBARS value was not critical.…”
Section: Resultsmentioning
confidence: 99%